A Guide to Brighter Phosphors‐Linking Luminescence Properties to Doping Homogeneity Probed by NMR. Issue 23 (7th November 2019) - Li, Wenyu; Adlung, Matthias; Zhang, Qianyun; Wickleder, Claudia; Schmedt auf der Günne, Jörn
Abstract: Crystalline powders of Ln 3+ doped LaPO4 (Ln=Nd, Gd, Dy, Ho, Er, Tm, Yb) have been synthesized to serve in a case study for linking doping homogeneity as determined by NMR to luminescent properties. Samples obtained via different synthesis methods act as examples of homo‐ and inhomogeneous doping. The sample quality was verified by X‐ray diffraction. The homogeneously doped samples show improved luminescent properties in terms of brightness and lifetime which is consistent with the interpretation that, NMR visibility curves probe the distribution of paramagnetic dopants on a similar length scale as necessary for an efficient energy transfer in crystalline phosphors i. e. between sensitizers and activators, and to killer sites. Thus "NMR homogeneity" as observed by visibility curves may serve as a tool to optimize luminescent materials. Abstract : NMR allows distinguishing homogeneous from heterogeneous doping situations, which makes phosphors convert light more efficiently.